A case study on slope instability of Punatshangchhu Hydroelectric Project Authority-I Dam in Bhutan - Lhamo, Rinchen (Bhutan Journal of Research and Development, 2022)
The stability of the slope is a greater concern to engineers and geoscientists as the socioeconomic consequences of the failures are huge. One such case is the slope instability of right bank of Punatshangchhu Hydroelectric Project Authority (PHPA-I) dam, Bhutan. The main geology of dam site is characterized by coarse-grained quartzo-feldspathic and biotite- muscovite gneiss. Since the start of the project in 2008, project encountered several geotechnical problems. During excavation at dam pit area, the shear zone got day-lighted which triggered a huge movement of right bank of dam in 2013. As such, project authority has carried out various stabilization measures in arresting movement of right abutment of dam. In this paper, subsurface profile construction from boring log data using Rockwork software (Rocscience) for PHPA-I dam site is presented. The subsurface profile once constructed can be used for identifying the critical slip surface and can also be used in modeling for slope stability analysis. Moreover, it can be a database for future use in that part of the study area.